Poverty Alleviation by Education is A Kind of Awakening and Discovery: In Memory of the “Poverty Alleviation War” of a Retired Middle School Principal in Eastern China - Hai, Yuhan (Science Insights Education Frontiers, 2021)
The development of education to improve poverty in the region has become an essential direction of the world’s poverty alleviation work. In the poverty alleviation by education work in China, educators who are on the front line of poverty are determined by education and nurturing their wisdom, leading countless children from families out of poverty and toward hope. In 2016, Liqun Chen, the principal who retired from a prestigious high school in eastern China loving the Miao Townships, insisted on combining poverty alleviation with supporting aspirations, using the love and responsibility of a “teacher” to inject new spirit into basic education in ethnic areas. He ignited dreams and hopes for children in frontier regions. This article elaborates on Liqun Chen’s help and aspirations in Taijiang County from the perspectives of students, teachers, and regions.